Comparative transcriptome profiling reveals the role of phytohormones and phenylpropanoid pathway in early-stage resistance against powdery mildew in watermelon (Citrullus lanatus L.) - Yadav, Vivek; Wang, Zhongyuan; Guo, Yanliang; Zhang, Xian (Frontiers in Plant Science, 2022)
Yield and fruit quality loss by powdery mildew (PM) fungus is a major concern in cucurbits, but early-stage resistance mechanisms remain elusive in the majority of cucurbits. Here, we explored the comparative transcriptomic dynamics profiling of resistant line ZXG-1755 (R) and susceptible line ZXG-1996 (S) 48 h post-inoculation in watermelon seedlings to pinpoint precise expression changes induced by P. xanthii race ‘2F’. Phenotypic responses were confirmed by microscopy and endogenous levels of defense and signaling related phytochromes were detected higher in resistant lines. In total, 7642 differently expressed genes (DEGs) were detected, and 57.27% of genes were upregulated in four combinations. DEGs were predominantly abundant in the KEGG pathway linked with phenylpropanoid biosynthesis, plant hormone and transduction, and phenylalanine metabolism, whereas GO terms of defense response, response to fungus, and chitin response were predominant in resistant lines, evidencing significant defense mechanisms and differences in the basal gene expression levels between these contrasting lines. The expression of selected DEGs from major pathways (hormonal, lignin, peroxidase, sugar) signaling pathways was validated via qRT-PCR. In short, our study portrayed strong evidence indicating the important role of a complex network associated with lignin biosynthesis and phytohormone related downstream mechanisms that are responsible for incompatible interaction between PM and watermelon resistance line.